Ultra-stable IrRu-doped NiSe array for highly efficient alkaline overall water electrolysis - Liwen Bie; Qiang Wang; Ruofei Du; Changxiang Shao; Tiansheng Mu; Xiaodong Zhu; Jian Gao (Chemical Engineering Journal, 2026)

Recombinant neuropeptide Y modulates neuroendocrine signaling, inflammation, antioxidant defense, and nitrite resistance in tilapia - Ziyan Liu; Ruyue Sun; Yang Yu; Jiaqi Li; Tiansheng Zhu; Meiqing Li; Caiyun Sun; Wensheng Li (Aquaculture, 2026)

Se vacancies-induced local microelectric field construction in Co3Se4-x and kinetics enhancement of zinc-iodine batteries - Lijun Tang; Yubing Sun; Changxiang Shao; Qiang Wang; Xiangyu Wang; Tiansheng Mu; Xiaodong Zhu; Jian Gao (Chemical Engineering Journal, 2026)

Establishment of a TaqMan qPCR assay for the rapid detection and quantification of Nocardia seriolae in aquaculture - Zexia Chen; Yang Yu; Tiansheng Zhu; Chaowei Song; Zijun Wang; Ziyan Liu; Ran Cai; Lei Luo; Xiangjun Miao; Wensheng Li; Caiyun Sun (Aquaculture, 2026)

Recombinant expression and identification of tilapia neuropeptide Y in Bacillus subtilis and its protective potential against ammonia stress - Ziyan Liu; Ruyue Sun; Yang Yu; Jiaqi Li; Tiansheng Zhu; Meiqing Li; Caiyun Sun; Wensheng Li (Aquaculture, 2026)

Nitrite exposure on gills of Oreochromis niloticus: structure change, immune response, and apoptosis - Chaowei Song; Tiansheng Zhu; Ran Cai; Yang Yu; Ziyan Liu; Jianing Yan; Yingying Lian; Jiaqi Li; Wensheng Li (Frontiers in Marine Science, 2025)
Nitrite is one of the most common pollutants in high-density aquaculture systems and has a potentially serious impact on the health of fish. The gill, as the organ directly in contact with the environment, performs several vital physiological functions, including gas exchange, osmotic pressure regulation, and mucosal immunity. Using a series of nitrite concentration gradients, we investigated the impact of nitrite on tilapia gills, with a focus on its immune responses. The results indicated that nitrite exposure could significantly increase the number of mucus cells and change the subtypes of chloride cells. Nitrite exposure significantly elevated serum catalase (CAT) activity and decreased superoxide dismutase (SOD) activity. After nitrite treatment, the expression of ion channel protein genes was markedly affected, with a substantial increase in Na + /Cl − cotransporter ( ncc ) expression. Inflammatory gene expression in the gill was also significantly altered. Both in vitro and in vivo experiments revealed that key genes in the IL-17 signaling pathway were considerably altered after nitrite exposure. Mitochondrial damage and apoptosis in the gill tissues were also found after nitrite exposure. In conclusion, nitrite exposure altered immune function and ion transport, especially the activation of the IL-17 signaling pathway, damage to mitochondrial structure, and apoptosis in the gill. This study enhances our understanding of the mechanisms underlying nitrite-induced damage to the gill.

Calycosin alleviates ovariectomy-induced osteoporosis by promoting BMSCs autophagy via the PI3K/Akt/mTOR pathway - Shouyu Xiang; Yinji Luo; Wei Liu; Cheng Tang; Tianyu Zhu; Lai Tian; Tiansheng Zheng; Long Ling; Mingyang Jia; Xing Li; Yanming Cao (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

N, O Co-doped porous carbon host with interconnected reaction microenvironments for long-life zinc-iodine batteries - Lijun Tang; Jian Gao; Tong Shen; Yubing Sun; Xiangyu Wang; Yongchao Zhang; Tiansheng Mu; Xiaodong Zhu (Chemical Engineering Journal, 2025)

Diversity of Wolbachia infection and its influence on mitochondrial DNA variation in the diamondback moth, Plutella xylostella - Xiangyu Zhu; Tiansheng Liu; Ao He; Ling Zhang; Jinyang Li; Tianpu Li; Xin Miao; Minsheng You; Shijun You (Molecular Phylogenetics and Evolution, 2023)

Higher BTX yield in coaromatization of n-hexane and methanol over [Zn,Ga]/HZSM-5 catalyst - Haibo Li; Bing Zhu; Xue Wang; Junmin Lv; Subing Fan; Tiansheng Zhao (Fuel, 2023)

First report of Cytospora tritici causing branch canker on English walnut in China - Shasha Xu; Rui Zhang; Deying Sun; Tiansheng Zhu; Xiaowei Chen; Xiaofei Chen; Xiaofei Chen (Journal of Plant Pathology, 2023)

Auxiliary thermodynamic analysis support capturing the differences in nanostructured FeVO4·nH2O electrodes between lithium and sodium ions storage mechanism - Linyi Zhao; Tiansheng Wang; Fei Li; Yongshuai Liu; Fengkai Zuo; Li Yang; Yifei Xu; Cunliang Zhang; Huaizhi Wang; Jie Liu; Xiaotong Dong; Shikai Zhu; et al. (Chemical Engineering Journal, 2023)

Novel EST-SSRs for an important quarantine pest Liriomyza sativae (Diptera: Agromyzidae) and their cross-species transferability - Tiansheng Liu; Xue Zhan; Jinyu Li; Fushi Ke; Xiangyu Zhu; Yanting Chen; Weiyi He; Shijun You (Applied Entomology and Zoology, 2022)

Monitoring of leaf nitrogen content of winter wheat using multi-angle hyperspectral data - Tiansheng Li; Zhen Zhu; Jing Cui; Jianhua Chen; Xiaoyan Shi; Xu Zhao; Menghao Jiang; Yutong Zhang; Weiju Wang; Haijiang Wang (International Journal of Remote Sensing, 2021)

Characterization and expression pattern analysis of pheromone receptor-like genes in Winter Mushroom Flammulina filiformis - Li Meng; Tiansheng Chou; Siyuan Jiang; Li Wang; Mengjuan Zhu; Irum Mukhtar; Baogui Xie; Wei Wang (Archives of Microbiology, 2020)

Anti-inflammatory effects of curcumin in experimental spinal cord injury in rats - Wei Jin; Jing Wang; Tiansheng Zhu; Baoyu Yuan; Hongbin Ni; Jian Jiang; Handong Wang; Weibang Liang (Inflammation Research, 2014)